Climate change in Europe: How to adapt our higher education curricula and involve the students – Learn4Green project - Van Loon, Karin; Kalambura, Sanja; Paixão, Susana; Ploomipuu, Inga; Rubić, Ivana; Mirenić, Ana (Crisis Management Days, 2025)
In response to the need to incorporate environmental and sustainability issues into higher education curricula, four European higher education institutions decided to combine their competences to build five ECTS international, collaborative, and multidisciplinary online course modules focusing on environment, sustainability, and health (energy crisis, analysis methods in the field of environment, green smart factories). The four partner institutions received an Erasmus+ subvention for a three-year period to develop an online course. These higher education institutions are Brussels-Brabant University College (Belgium), University of Applied Sciences Velika Gorica, (Croatia), Polytechnico Institut – Coimbra (Portugal) and Tartu Health Care College – Tartu (Estonia). The course's objective is to foster students' interest and develop the scientific, technological, and socio-political foundations in the fields of environment, sustainability, and health as well as communication, English language and crisis management skills. The project closely aligns with the European Strategy on Multilingualism and broader EU policies promoting foreign language learning and soft skills development. The teachers and students worked together in a co-construction way, using a situated learning environment. The process involved the teachers and students in a co-construction way, through a situated learning environment. This paper aims to present the methodology and partial results after one year, based on both quantitative and qualitative indicators.